Lost and found: dynamics of relationship and employment status over time in people with affective and psychotic spectrum disorders - Fanny Senner; Lisa Kerkhoff; Kristina Adorjan; Michael Lauseker; Monika Budde; Maria Heilbronner; Janos L. Kalman; Mojtaba Oraki Kohshour; Sergi Papiol; Daniela Reich-Erkelenz; Sabrina K. Schaupp; Eva C. Schulte; et al. (BJPsych Open)
Background Employment and relationship are crucial for social integration. However, individuals with major psychiatric disorders often face challenges in these domains.